Entrepreneurial intention of local community in Lenggong Valley, Malaysia - Jaafar, Mastura; Dahalan , Norziani; Mohd Rosdi, Siti Asma’ (2013)
Entrepreneurship is important to boost the socio-economic development. Most developing countries have successfully implemented social and economic development program to increase the living standards of the poor. Lenggong Valley is a new developing rural tourism attraction. The acknowledgement as a heritage site by UNESCO in July 2012 would definitely provide various business opportunities for the local community. Entrepreneurial intention (EI) has been receiving a significant intention among researchers since 1980’s. The term EI refers to specific action taken by individual towards achieving its specific target goals. Previous research on EI has been conducted in academic setting focusing on university students in various countries. Looking from different perspective, this study explore on possible variables (attitude, social norm and perceived behavioral control) that determine the EI of local community in tourism business development. The Data collection has been conducted on 500 local populations in Lenggong Valley and analyzed by using factor analysis. The rotated component analysis resulted 6 factors comprise of attitude toward money, attitude toward start-up, capital access, embeddedness, emotional intelligent and intention to be entrepreneur.